Pethidine and bupivacaine spinal anaesthesia: a comparative evaluation of postoperative complications and recovery profile - Udonquak, Mbuotidem M.; Kalu, Queeneth N.; Eshiet, Atim I. (International Journal of Research in Medical Sciences, 2017)
Background: Bupivacaine is commonly used as a sole agent for spinal anaesthesia unlike Pethidine. This study compares the immediate postoperative complications and recovery profile following spinal anaesthesia with pethidine and bupivacaine. Methods: Fifty-two patients who required short duration surgical procedures below the umbilicus were randomized to receive spinal anaesthesia with pethidine 1mg/Kg and 2.5 mL 0.5% bupivacaine. Time to recovery of pin prick sensation at S2, plantar flexion, proprioception of the big toe, and full motor recovery were compared for the two agents. Complications of pain, sedation, nausea and vomiting, pruritus and urinary retention in the immediate postoperative period were also compared. Results: Comparing Pethidine and Bupivacaine, time to return of pinprick sensation at S2 was 94.62±20.25 and 205.96±31.05 minutes respectively; return of plantar flexion was 92.88±12.01 and 193.85±39.56 minutes respectively; recovery of proprioception of the big toe was 31.15±9.41 and 172.50±42.70 minutes respectively; complete motor recovery was 47.89±14.08 and 221.73±44.72 minutes respectively. All the differences in recovery times were statistically significant (p<0.0001). There was no statistically significant difference in the incidence of pain and sedation. Only 4 (15.38%) patients in the Bupivacaine group experienced mild pain. There was no incident of nausea and vomiting. However, pethidine group experienced pruritus (19.22%) and bupivacaine group none. Bupivacaine group also had urinary retention (11.54%), while pethidine group had none. These differences were statistically significant (p=0.01). Conclusions: Pethidine exhibited a shorter recovery profile than Bupivacaine and also caused no significant complication in the immediate postoperative period.